Tanggung Jawab Hukum Keimigrasian Dalampengawasan Tenaga Kerja Asing Menurut Hukum Positif Indonesia - Fitria Wulandari; Lalu Husni; Rahmawati Kusuma (Fakultas Hukum Universitas Mataram, 2023)
This research aims are to analyse and to understand how is the arrangement of Immigration office supervisory on foreign manpower according to Indonesian positive laws. Applied method in this study was normative legal research which primarily conducted through library research and assessing related statutes. Result of this study shows that, regulations on the supervisory office conducted by the immigration office are based on the Law Number 11 of 2011 on Immigration and its implementing regulation, Presidential Regulation Number 34 of 2021 on the Employment of Foreign Manpower and completed with Law Number 13 of 2003 on Manpower. Immigration responsibility in conducting immigration actions is carried out by administrative and criminal actions. In order to guarantee legal certainty and justice for foreigners who are subject to immigration measures, the decision shall be stipulated in written form, which contains the identity of the person affected by the immigration action, the reasons for the action and the type of action, and may submit an objection to the said immigration action. The purpose of this immigration action is to carry out supervisory policies in the field of immigration and assist the implementation of law enforcement in the territory of the Republic of Indonesia, both preventive and repressive in nature.